STRATEGY ANALYSIS OF THE ZAKAT DISTRIBUTION SYSTEM IN BAZNAS LANGKAT DISTRICT USING THE SWOT QSPM MODEL - Gustianda, Putra Rizky; Rahma, Tri Inda Fadila; Tanjung, Ahmad Muhaisin B. Syarbaini (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
BAZNAS Langkat Regency distributes zakat to facilitate and expedite the distribution of zakat funds from muzakki to mustahik so that it is right on target and in accordance with the needs of mustahik, so the aim of the research is to develop a strategy for the zakat distribution system so that it can help distribute zakat funds better at BAZNAS Langkat Regency . This research uses a descriptive qualitative approach with the SWOT matrix and Quantitative Strategic Planning Matrix (QSPM), for SWOT respondents namely Amil zakat, Muzakki, Mustahik, and Langkat Regency Community, while for QSPM respondents namely Distribution Experts, HR Experts, and Experts in the field Finance. Based on the research results, alternative strategies obtained are creating a team to evaluate and supervise the empowerment of zakat distribution, increasing socialization and regional reach to increase fund collection, collaborating with local government to increase distribution reach, increasing the use of technology by utilizing social media and personalizing, maintaining image and quality of Baznas, creating a new program, namely productive distribution of zakat, improving the quality of human resources with training programs, creating a public complaint box, improving service quality to increase networks and relationships and holding weekly meetings for evaluation. Results The recommended strategy from this analysis is to create a team to evaluate and supervise the empowerment of zakat distribution at BAZNAS Langkat Regency with a Total Attractive Score of 15,358.